Pilot Safety and Feasibility Study of Non-invasive Limb Proprioceptive Cerebellar Stimulation for Epilepsy - Harper, Ronald M.; Hertling, Dieter; Curtis, Ashley; Sauerland, Eberhardt K.; De Giorgio, Christopher M. (Frontiers in Neurology, 2021)
Cerebellar stimulation reduces seizures in animals and in humans with drug-resistant epilepsy. We applied continuous cutaneous vibratory stimulation to foot limb proprioceptive receptors to activate cerebellar, pontine, and thalamic structures in drug-resistant epilepsy patients for 8-hrs nocturnally up to 6-months after a 4-week pre-treatment control baseline. Seizure frequency was evaluated during the baseline control period, and at six, twelve, and twenty-four weeks after the control recordings. Five-subjects completed at least the first 6-week treatment. At 12-weeks, the mean seizure reduction was -28.0%; two subjects continued for 24 weeks, with a decline of -44.1 and -45.4%. Limb proprioceptive stimulation offers a non-invasive intervention to reduce seizures in people with epilepsy.